Seed transfer modeling to support assisted population migration of white spruce: Do survival and tree age matter? - Lahcen Benomar; William C. Parker; Jean Bousquet; John Pedlar; Yuhui Weng; Raed Elferjani; Rongzhou Man; Steve Colombo (Forest Ecology and Management, 2026)

MIL-53(Fe)-mediated persulfate activation for the removal of pesticides-contaminated water: phytotoxicity evaluation, theoretical reactivity prediction and by-products degradation pathways - Muriel R. Affonso; Igor G.S. Oliveira; Fernando C. Gallina; Beatriz T. Marin; João P.P. Encide; Micael M. Baruch; Robson S. Souto; Renata Colombo; Kathia M. Honorio; Marcos R.V. Lanza; Willyam R.P. Barros (Chemical Engineering Journal, 2026)

Isotopic insights into the fate of atmospheric nitrogen in alpine tundra ponds with contrasting land cover and cryospheric conditions - R. Balestrini; N. Colombo; M. Freppaz; M.F. Lehmann; C. Delconte; E. Pintaldi; F. Salerno; I. Matiatos (CATENA, 2026)

Corrigendum to “Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil)” [J. Geochem. Explor. 281,107934 (2026)] - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Interpreting the willingness and ability of rural producers to engage in conservation efforts in the Chaco forest of Argentina - Cristina C. Nuñez Godoy; Gisela S. Córdoba; Federico Colombo Speroni; Leonidas O. Girardin (Ecological Economics, 2026)

Treatment of veterinary insecticide residues using biomixtures: performance, degradation kinetics, and ecotoxicological assessment - R. C. Pessagno; N. Olié; V. A. Silvani; R. P. Colombo; G. Svartz; A. Iriel (International Journal of Environmental Science and Technology, 2026)

Flower-like WO3-modified Vulcan carbon GDEs for photoelectro-Fenton process: Efficient ciprofloxacin degradation and mechanistic insights - João Paulo C. Moura; Vanessa S. Antonin; Caio Machado Fernandes; Aline B. Trench; Erica S. Conrado; Michell O. Almeida; Kathia M. Honorio; Renata Colombo; Rafael Sotana; Ana M.P. Neto; Mauro C. Santos (Journal of Environmental Management, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil) - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Perspectives on abiotic ecosystem services provided by glacial lakes in high-mountain areas - C. Viani; N. Colombo; M. Rogora; M. Giardino; M. Freppaz; I.M. Bollati (Ecosystem Services, 2025)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Electrochemical degradation of tebuthiuron pesticide using a flow reactor: Insights into the co-generation of oxidants and ecotoxicological risks - Robson S. Souto; Isaac Sánchez-Montes; Géssica O.S. Santos; Paulo J.M. Cordeiro-Junior; Renata Colombo; Mauro C. Santos; Marcos R.V. Lanza (Journal of Environmental Chemical Engineering, 2025)

Telescopic alluvial fans and pleistocene-holocene temporary lakes in the quebradas del Río Toro and Tastil (Salta, NW Argentina): main sedimentary features - F. Colombo; J. A. Salfity; M. C. Sánchez (Journal of Iberian Geology, 2025)
The Toro and Tastil Quebradas (river valleys) present different terrace-like geoforms made up of deposits of coarse-grained clastic materials. These terraces display convex-upward surfaces, a highly variable distribution, have a small lateral extension and depend on the lithology of the geological basement, which differs significantly along the quebradas . The number of terraces between one area and another indicates that these terraced geoforms should not be ascribed to one single cause, but rather to a variety of factors, i.e. local variations at base-level. The coarse-grained materials of the terraces are usually arranged in roughly horizontal layers that characterize the outcrops. These are interfingered with fine-grained mud-rich materials. The freshwater gastropod remains in the mud-rich materials indicate that they accumulated in lacustrine-like sedimentary environments. These developed from alluvial fans that spread out from the lateral quebradas to occupy the entire main valley (q uebrada) , giving rise to natural dams and temporary lakes upstream. Absolute data obtained by radiocarbon ( 14 C) methods strongly suggest that the alluvial fans were coeval with the temporary lakes in the Upper Pleistocene - Middle Holocene. The El Niño Southern Oscillation (ENSO) effects could have brought about the local variations in base-level that generated the younger temporary lakes, whereas the older ones were probably controlled by precession cycles (at about 21,000 y). The large number of temporary lakes scattered across the region suggests the overlapping of forcing factors at local and regional scales.

Reviewing factors that influence voluntary participation in conservation programs in Latin America - Cristina C. Nuñez Godoy; Federico Colombo Speroni; Mauricio Nuñez-Regueiro; Leonidas Osvaldo Girardin (Forest Policy and Economics, 2024)

Retrieval of snow liquid water content from radiative transfer model, field data and PRISMA satellite data - C. Ravasio; R. Garzonio; B. Di Mauro; E. Matta; C. Giardino; M. Pepe; E. Cremonese; P. Pogliotti; C. Marin; R. Colombo (Remote Sensing of Environment, 2024)

An aquaculture risk model to understand the causes and consequences of Atlantic Salmon mass mortality events: A review - Zaman Sajid; A. Kurt Gamperl; Christopher C. Parrish; Stefanie M. Colombo; Javier Santander; Charles Mather; Barbara Neis; Ingunn Marie Holmen; Ramón Filgueira; Cynthia H. McKenzie; Lissandra Souto Cavalli; Mohamed Jeebhay; et al. (Reviews in Aquaculture, 2024)
Mass mortality events (MMEs) are defined as the death of large numbers of fish over a short period of time. These events can result in catastrophic losses to the Atlantic salmon aquaculture industry and the local economy. However, they are challenging to understand because of their relative infrequency and the high number of potential factors involved. As a result, the causes and consequences of MMEs in Atlantic salmon aquaculture are not well understood. In this study, we developed a structural network of causal risk factors for MMEs for aquaculture and the communities that depend on Atlantic salmon aquaculture. Using the Interpretive Structural Modeling (ISM) technique, we analysed the causes of Atlantic salmon mass mortalities due to environmental (abiotic), biological (biotic) and nutritional risk factors. The consequences of MMEs were also assessed for the occupational health and safety of aquaculture workers and their implications for the livelihoods of local communities. This structural network deepens our understanding of MMEs and points to management actions and interventions that can help mitigate mass mortalities. MMEs are typically not the result of a single risk factor but are caused by the systematic interaction of risk factors related to the environment, fish diseases, feeding/nutrition and cage‐site management. Results also indicate that considerations of health and safety risk, through pre‐ and post‐event risk assessments, may help to minimize workplace injuries and eliminate potential risks of human fatalities. Company and government‐assisted socio‐economic measures could help mitigate post‐mass mortality impacts. Appropriate and timely management actions may help reduce MMEs at Atlantic salmon cage sites and minimize the physical and social vulnerabilities of workers and local communities.

Zircon U-Pb and Lu-Hf isotopes reveal the crustal evolution of the SW Angolan Shield (Congo Craton) - Ezequiel Ferreira; Jérémie Lehmann; José Feliciano Rodrigues; Ben Hayes; Enrique Merino-Martínez; Lorenzo Milani; Grant M. Bybee; Trishya M. Owen‑Smith; José Luis García-Lobón; Colombo C. G. Tassinari; Henriette Ueckermann; Kei Sato; et al. (Gondwana Research, 2024)

Unveiling Trichosporon austroamericanum sp. nov.: A Novel Emerging Opportunistic Basidiomycetous Yeast Species - Elaine C. Francisco; Marie Desnos-Ollivier; Chendo Dieleman; Teun Boekhout; Daniel Wagner de C. L. Santos; José O. Medina-Pestana; Arnaldo L. Colombo; Ferry Hagen (Mycopathologia, 2024)
During an epidemiological survey, a potential novel species within the basidiomycetous yeast genus Trichosporon was observed. The clinical strain was obtained from a urine sample taken from a Brazilian kidney transplant recipient. The strain was molecularly identified using the intergenic spacer (IGS1) ribosomal DNA locus and a subsequent phylogenetic analysis showed that multiple strains that were previously reported by other studies shared an identical IGS1-genotype most closely related to that of Trichosporon inkin . However, none of these studies provided an in-depth characterization of the involved strains to describe it as a new taxon. Here, we present the novel clinically relevant yeast for which we propose the name Trichosporon austroamericanum sp. nov. (holotype CBS H-24937). T. austroamericanum can be distinguished from other siblings in the genus Trichosporon using morphological, physiological, and phylogenetic characters.

When another one bites the dust: Environmental impact of global copper demand on local communities in the Atacama mining hotspot as registered by tree rings - Nicolás C. Zanetta-Colombo; Tobias Scharnweber; Duncan A. Christie; Carlos A. Manzano; Mario Blersch; Eugenia M. Gayo; Ariel A. Muñoz; Zoë L. Fleming; Marcus Nüsser (Science of The Total Environment, 2024)

The use of a complex tetra-culture alveolar model to study the biological effects induced by gold nanoparticles with different physicochemical properties - Melissa Saibene; Tommaso Serchi; Patrizia Bonfanti; Anita Colombo; Inge Nelissen; Rashi Halder; Jean-Nicolas Audinot; Beatriz Pelaz; Mahmoud G. Soliman; Wolfgang J. Parak; Paride Mantecca; Arno C. Gutleb; et al. (Environmental Toxicology and Pharmacology, 2024)

High-Resolution In Situ Characterization of the Hydrochemical Variability Along the Fluvio-marine Transition of the Río de la Plata Estuary, Argentina - S. Heguilor; E. D. Speranza; L. M. Tatone; C. N. Skorupka; M. C. Migoya; J. C. Colombo (Estuaries and Coasts, 2024)

Hymenopteran parasitoids of black soldier fly Hermetia illucens (L.) (Diptera: Stratiomyidae) in chicken farms with two new species from India - C. Binoy; Gérard Delvare; Wesley D. Colombo; K.S. Surya; P.M. Sureshan (Journal of Asia-Pacific Entomology, 2023)

Wheat craft beer made from AFB1-contaminated wheat malt contains detectable mycotoxins, retains quality attributes, but differs in some fermentation metabolites - Fabrícia França Bezerril; Tatiana Colombo Pimentel; Karine Peixoto de Aquino; Danieli C. Schabo; Marcy Heli Paiva Rodrigues; Marcos dos Santos Lima; Donald W. Schaffner; Eliana B. Furlong; Marciane Magnani (Food Research International, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Identification of IPT9 in Brachiaria brizantha (syn. Urochloa brizantha) and expression analyses during ovule development in sexual and apomictic plants - Luciana G. Ferreira; Diva M. A. Dusi; André S. T. Irsigler; Ana C. M. M. Gomes; Lilian H. Florentino; Marta A. Mendes; Lucia Colombo; Vera T. C. Carneiro (Molecular Biology Reports, 2023)
Background In Brachiaria sexual reproduction, during ovule development, a nucellar cell differentiates into a megaspore mother cell (MMC) that, through meiosis and mitosis, gives rise to a reduced embryo sac. In aposporic apomictic Brachiaria , next to the MMC, other nucellar cells differentiate into aposporic initials that enter mitosis directly forming an unreduced embryo sac. The IPT (isopentenyltransferase) family comprises key genes in the cytokinin (CK) pathway which are expressed in Arabidopsis during ovule development. BbrizIPT9 , a B. brizantha ( syn. Urochloa brizantha ) IPT9 gene, highly similar to genes of other Poaceae plants, also shows similarity with Arabidopsis IPT9, AtIPT9 . In this work, we aimed to investigate association of BbrizIPT9 with ovule development in sexual and apomictic plants. Methods and results RT-qPCR showed higher BbrizIPT9 expression in the ovaries of sexual than in the apomictic B. brizantha . Results of in-situ hybridization showed strong signal of BbrizIPT9 in the MMC of both plants, at the onset of megasporogenesis. By analyzing AtIPT9 knockdown mutants, we verified enlarged nucellar cell, next to the MMC, in a percentage significantly higher than in the wild type, suggesting that knockout of AtIPT9 gene triggered the differentiation of extra MMC-like cells. Conclusions Our results indicate that AtIPT9 might be involved in the proper differentiation of a single MMC during ovule development. The expression of a BbrizIPT9 , localized in male and female sporocytes, and lower in apomicts than in sexuals, and effect of IPT9 knockout in Arabidopsis, suggest involvement of IPT9 in early ovule development.

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Nanopore Genome Sequencing and Variant Analysis of the Susceptible Candida auris Strain L1537/2020, Salvador, Brazil - Auke W. de Jong; Elaine C. Francisco; João Nóbrega de Almeida; Igor B. Brandão; Felicidade M. Pereira; Pedro H. Presta Dias; Magda M. de Miranda Costa; Regiane T. de Souza Jordão; Duong Vu; Arnaldo L. Colombo; Ferry Hagen (Mycopathologia, 2021)
Candida auris has been reported worldwide, but only in December 2020, the first strain from a COVID-19 patient in Brazil was isolated. Here, we describe the genome sequence of this susceptible C. auris strain and performed variant analysis of the genetic relatedness with strains from other geographic localities.

Molecular Identification and Antimicrobial Activity of Foliar Endophytic Fungi on the Brazilian Pepper Tree (Schinus terebinthifolius) Reveal New Species of Diaporthe - Germana D. dos Santos; Renata R. Gomes; Rosana Gonçalves; Gheniffer Fornari; Beatriz H. L. N. S. Maia; Claudia Schmidt-Dannert; Francois Gaascht; Chirlei Glienke; Gabriela X. Schneider; Israella R. Colombo; Juliana Degenhardt-Goldbach; João L. M. Pietsch; et al. (Current Microbiology, 2021)

Freshwater, Landlocked Grand Lake Strain of Atlantic Salmon (Salmo salar L.) as a Potential Genetic Source of Long Chain Polyunsaturated Fatty Acids Synthesis - Stefanie M. Colombo; Mohamed Emam; Brian C. Peterson; Jennifer R. Hall; Gary Burr; Zeyu Zhang; Matthew L. Rise (Frontiers in Marine Science, 2021)
Selection efforts focused on adaptation to plant-based diets, particularly the ability to synthesize polyunsaturated fatty acids (PUFA), are now emerging in aquaculture. Landlocked salmon (Grand Lake population; GL) may differ from the commercial Saint John River (SJR) strain in terms of PUFA metabolism. The objective of this study was to determine if GL salmon can contribute toward broodstock selection for enhanced PUFA synthesis. Two diets containing either fish oil (FO) or plant-based oil (FO-free) were fed to the SJR and GL strains (∼58 g/fish) for 16 weeks. Growth, liver, and muscle fatty acid (FA) content, and transcript expression of lipid metabolism and inflammation-related genes were evaluated. GL salmon fed the FO diet showed reduced growth compared to SJR salmon (fed either diet); however, GL salmon fed the FO-free diet, growth was not significantly different compared to any group. In liver, SJR salmon fed the FO-free diet had higher levels of n-6 PUFAs (21.9%) compared to GL fed the same diet (15.9%); while GL salmon fed the FO-free diet had higher levels of monounsaturated FAs (48.9%) compared with SJR salmon fed the same diet (35.7%). 20:5n-3 and 22:6n-3 were the same in GL and SJR salmon liver and muscle, respectively, fed the FO-free diet. In liver, GL salmon fed the FO-free diet had higher acac and acly compared to all treatments and had higher fasb compared to both strains fed the FO-diet. GL salmon fed the FO-free diet had higher cd36c and fabp3b in liver compared to GL salmon fed the FO diet and SJR salmon fed either diet. GL salmon fed the FO-free diet had higher lect2a and pgds in liver compared to SJR salmon fed the FO-free diet. In muscle, GL salmon fed the FO-free diet had higher fadsd5 and fadsd6b compared with both strains fed the FO diet. These results suggest there is a genetic basis behind the potential for GL salmon to utilize FO-free diets more efficiently than SJR salmon, with regards to FA metabolism.

The use of biomimetic tools for water quality monitoring: passive samplers versus sentinel organisms - M. Morrone; N. E. Cappelletti; L. M. Tatone; M. J. Astoviza; J. C. Colombo (Environmental Monitoring and Assessment, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Coupled Modeling of Sedimentary Basin and Geomechanics: A Modified Drucker–Prager Cap Model to Describe Rock Compaction in Tectonic Context - N. Guy; D. Colombo; J. Frey; T. Cornu; M. C. Cacas-Stentz (Rock Mechanics and Rock Engineering, 2019)

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

Elucidating the symbiotic interactions between a locally isolated microalga Chlorella vulgaris and its co-occurring bacterium Rhizobium sp. in synthetic municipal wastewater - L. Ferro; M. Colombo; E. Posadas; C. Funk; R. Muñoz (Journal of Applied Phycology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Ambrosia pollen source inventory for Italy: a multi-purpose tool to assess the impact of the ragweed leaf beetle (Ophraella communa LeSage) on populations of its host plant - M. Bonini; Branko Šikoparija; C. A. Skjøth; G. Cislaghi; P. Colombo; C. Testoni; M. Smith (International Journal of Biometeorology, 2018)

Expression of the Parkinson’s Disease-Associated Gene Alpha-Synuclein is Regulated by the Neuronal Cell Fate Determinant TRIM32 - Maria Angeliki S. Pavlou; Nicoló Colombo; Sandra Fuertes-Alvarez; Sarah Nicklas; Laura Gonzalez Cano; Maria C. Marín; Jorge Goncalves; Jens C. Schwamborn (Molecular Neurobiology, 2017)

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

The growth and contamination mechanism of the Cana Brava layered mafic-ultramafic complex: new field and geochemical evidences - Tommaso Giovanardi; Vicente A. V. Girardi; Ciro T. Correia; Silvano Sinigoi; Colombo C. G. Tassinari; Maurizio Mazzucchelli (Mineralogy and Petrology, 2017)

Healthy and tumoral tissue resistivity in wild-type and sparc–/– animal models - D. Meroni; G. Mauri; D. Bovio; A. M. Bianchi; C. Chiodoni; M. P. Colombo; E. Meroni; A. Aliverti (Medical & Biological Engineering & Computing, 2016)

Fatty acid alterations in the detritivorous Prochilodus lineatus promoted by opportunistic feeding on sewage discharges in the R ío de la P lata estuary - E. D. Speranza; M. Colombo; L. M. Tatone; N. Cappelletti; M. C. Migoya; J. C. Colombo (Journal of Fish Biology, 2016)
Muscle fatty acid profiles and PCB contents of the detritivorous species Prochilodus lineatus and its diet (stomach contents, settling particles and sediments) were analysed from reference and polluted areas of the Paraná‐Rio de la Plata basin, to evaluate the alterations produced by opportunistic feeding on sewage discharges. Overall muscle fatty acid composition was dominated by saturated and monounsaturated 16 and 18 carbon (18 C‐ FA ) components with reduced long‐chain polyunsaturated fatty acids ( LC‐PUFA ). Compared to sediments, settling particles and stomach contents were enriched in lipids and had a similar fatty acid composition. Opportunistic feeding on sewage detritus at Buenos Aires resulted in enhanced PCB and triglyceride accumulation, with higher proportions of 18 C‐ FA and lower proportions of 16:1 and LC‐PUFA compared to fish from northern pristine reaches of the basin. Mid‐Paraná showed intermediate values reflecting mixing of the North stock with migrating Buenos Aires P. lineatus identified by their lipid and contaminant profile. According to multivariate analyses, this geographical variation of fatty acid composition was strongly influenced by PCB concentration. Prochilodus lineatus assimilates the energy subsidy of sewage inputs through enhanced lipogenesis with dominant 18 C‐ FA and significant amounts of valuable LC‐PUFA . This lipid alteration facilitates the bioaccumulation of PCBs which in turn may reinforce the adipogenic effect of sewage feeding.

Paediatric nasopharyngeal cytology: a new diagnostic opportunity? - S. Torretta; P. Marchisio; M. R. Colombo; C. Rosazza; L. Pignataro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A follow-up study examining airborne Ambrosia pollen in the Milan area in 2014 in relation to the accidental introduction of the ragweed leaf beetle Ophraella communa - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; Ł. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2016)

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Is the recent decrease in airborne Ambrosia pollen in the Milan area due to the accidental introduction of the ragweed leaf beetle Ophraella communa? - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; L. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2015)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Seasonal and inter-annual variability of water quality in the Uruguay River, Argentina - Juan C. Colombo; Carlos N. Skorupka; Claudio Bilos; Leandro Tatone; Natalia Cappelletti; M. Carolina Migoya; Malena Astoviza; Eric Speranza (Hydrological Sciences Journal, 2015)

Timing of multiple hydrothermal events in the iron oxide–copper–gold deposits of the Southern Copper Belt, Carajás Province, Brazil - Carolina P. N. Moreto; Lena V. S. Monteiro; Roberto P. Xavier; Robert A. Creaser; S. Andrew DuFrane; Gustavo H. C. Melo; Marco A. Delinardo da Silva; Colombo C. G. Tassinari; Kei Sato (Mineralium Deposita, 2015)

Bioaccumulation of dioxin-like PCBs and PBDEs by detritus-feeding fish in the Rio de la Plata estuary, Argentina - N. Cappelletti; E. Speranza; L. Tatone; M. Astoviza; M. C. Migoya; J. C. Colombo (Environmental Science and Pollution Research, 2015)

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

Deficits in memory and visuospatial learning correlate with regional hippocampal atrophy in MS - Giulia Longoni; Maria A. Rocca; Elisabetta Pagani; Gianna C. Riccitelli; Bruno Colombo; Mariaemma Rodegher; Andrea Falini; Giancarlo Comi; Massimo Filippi (Brain Structure and Function, 2015)

Performance of Bemisia tabaci (Genn.) Biotype B (Hemiptera: Aleyrodidae) on Weeds - L D M Sottoriva; A L Lourenção; C A Colombo (Neotropical Entomology, 2014)

Behavior of Dioxin Like PCBs and PBDEs During Early Diagenesis of Organic Matter in Settling Material and Bottom Sediments from the Sewage Impacted Buenos Aires’ Coastal Area, Argentina - N. Cappelletti; C. N. Skorupka; M. C. Migoya; L. Tatone; M. Astoviza; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

BbrizAGL6 Is Differentially Expressed During Embryo Sac Formation of Apomictic and Sexual Brachiaria brizantha Plants - Larissa Arrais Guimarães; Diva Maria de A. Dusi; Simona Masiero; Francesca Resentini; Ana Cristina M. M. Gomes; Érica Duarte Silveira; Lilian Hasegawa Florentino; Júlio Carlyle M. Rodrigues; Lucia Colombo; Vera Tavares de C. Carneiro (Plant Molecular Biology Reporter, 2013)

Differential efficiency of two strains of the arbuscular mycorrhizal fungus Rhizophagus irregularis on olive (Olea europaea) plants under two water regimes - M. J. Bompadre; M. C. Rios De Molina; R. P. Colombo; L. Fernandez Bidondo; V. A. Silvani; A. G. Pardo; J. A. Ocampo; A. M. Godeas (Symbiosis, 2013)

Molecular Identification of Melanised Non-Sporulating Moulds: A Useful Tool for Studying the Epidemiology of Phaeohyphomycosis - Daniel W. C. L. Santos; Ana Carolina B. Padovan; Analy S. A. Melo; Sarah S. Gonçalves; Viviane R. Azevedo; Marilia M. Ogawa; Tainá Veras Sandes Freitas; Arnaldo L. Colombo (Mycopathologia, 2013)

Trace Metals in Settling Particles from the Sewage Impacted Buenos Aires Coastal Area in the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2013)

Migratory behaviour of a dominant detritivorous fish Prochilodus lineatus evaluated by multivariate biochemical and pollutant data - E. D. Speranza; N. Cappelletti; M. C. Migoya; L. M. Tatone; J. C. Colombo (Journal of Fish Biology, 2012)
This paper studies the migration pathways and ranges of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Río de la Plata basin using multivariate analysis of biochemical and pollutant data. Biochemical composition (water, ash, lipids, proteins, carbohydrates, neutral lipids classes and fatty acids), aliphatic hydrocarbons (ALI), polychlorinated biphenyls (PCB), linear alkylbenzenes (LAB) and organochlorine pesticides (OClP) were determined in muscle samples of P. lineatus collected in Metropolitan Buenos Aires, the lower Paraná River (Paraná: 200–1000 km from Buenos Aires) and the middle Paraná and Paraguay Rivers (North: 1000–1400 km north). Biochemical variables and pollutants exhibited large variability [Lipids 1·1–89·5% wet mass; ALI 1·4–413; LABs not detectable (n.d.)–115·2; PCBs n.d.–27·9; OClPs n.d.–11·8 µg g −1 dry mass], due to the contrast of Buenos Aires with North fish. Fish from Buenos Aires were fatty (lipids 24·7 ± 12·3% wet mass), enriched in 18 carbon fatty acids and severely contaminated (ALI 152·4 ± 72·3; LABs 65·1 ± 26·4; PCBs 15·2 ± 6·8; OClPs 1·8 ± 1·9 µg g −1 dry mass mean ± s.d .). In contrast, fish from North were lean (4·1 ± 3·1% wet mass), enriched in long chain (>20 carbons) polyunsaturated fatty acids, with average one to two orders of magnitude lower pollutant levels (ALI 41·2 ± 51·9; PCBs 2·2 ± 3·5; LABs 8·8 ± 21·1; OClPs 0·67 ± 0·75 µg g −1 dry mass mean ± s.d .). Paraná showed intermediate values in all variables, denoting the mixing of different fish stocks. Based on principal component analysis, 14 outliers from 60 North and Paraná samples (representing 26 from 108 individual fish) were identified as pertaining to the Buenos Aires group with very similar lipid and pollutant levels. Data suggest that P. lineatus migrates a highly variable distance, exceeding 800–1000 km in multiple spatial and temporal overlapping ranges. Chemometric analysis of biochemical and pollutant data effectively discriminates fish according to the chemical signature acquired by detritus feeding in pristine and contaminated urban or industrial areas.

Pingüino In-bearing polymetallic vein deposit, Deseado Massif, Patagonia, Argentina: characteristics of mineralization and ore-forming fluids - Sebastián M. Jovic; Diego M. Guido; Isidoro B. Schalamuk; Francisco J. Ríos; Colombo C. G. Tassinari; Clemente Recio (Mineralium Deposita, 2011)

Metamorphic P-T evolution of granulites in the central Ribeira Fold Belt, SE Brazil - Telmo M. Bento dos Santos; José M. Munhá; Colombo C. G. Tassinari; Paulo E. Fonseca; Coriolano Dias Neto (Geosciences Journal, 2011)

Remote sensing of larch phenological cycle and analysis of relationships with climate in the Alpine region - L. BUSETTO; R. COLOMBO; M. MIGLIAVACCA; E. CREMONESE; M. MERONI; M. GALVAGNO; M. ROSSINI; C. SINISCALCO; U. MORRA DI CELLA; E. PARI (Global Change Biology, 2010)
This research aims at developing a remote sensing technique for monitoring the interannual variability of the European larch phenological cycle in the Alpine region of Aosta Valley (Northern Italy) and to evaluate its relationships with climatic factors. Phenological field observations were conducted in eight test sites from 2005 to 2007 to determine the dates of completion of different phenological phases. MODerate Resolution Imaging Spectrometer (MODIS) 250 m 16‐days normalized difference vegetation index (NDVI) time series were fitted with double logistic curves and the dates corresponding to different features of the curves were determined. Comparison with field data showed that the features of the fitted NDVI curve that allowed the best estimate of the start and end of the growing season were the zeroes of its third derivative (MAE of 6 and 4 days, respectively). The start and end of season were also estimated with the spring warming (SW) and growing season index (GSI) phenological models. MODIS start and end of season dates generally agreed with those obtained by the SW and GSI climate‐driven phenological models. However, phenological models provided erroneous results when applied in years with anomalous meteorological conditions. The relationships between interannual variability of the larch phenological cycle and climate were investigated by comparing the mean start and end of season yearly anomalies with air temperature anomalies. A strong linear relationship ( R 2 =0.91) was found between mean spring temperatures and mean start of season dates, with an increase of 1 °C in mean spring temperature leading to a 7‐day anticipation of mean larch bud‐burst date. Leaf coloring dates were found to be best related with mean September temperature ( R 2 =0.77), but with higher spring temperatures appearing to lead to earlier leaf coloring.

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Vertical Fluxes and Accumulation of Trace Metals in Superficial Sediments of the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2009)

Biochemical composition of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Paraná‐Río de la Plata Basin - E. D. Speranza; J. C. Colombo (Journal of Fish Biology, 2009)
The biochemical composition of muscle, liver and stomach contents of a detritivorous fish Prochilodus lineatus was analysed and compared to settling particles and sediments along pollution gradients over 1500 km of the Río de la Plata Basin to evaluate the effects of anthropogenic discharges in a detritus food chain. The stomach contents of P. lineatus collected in the polluted Metropolitan Buenos Aires coast were enriched in proteins, carbohydrates and lipids, similar to settling particulates collected in the sewer area, and two to five times higher than underlying sediments, supporting the interpretation that P. lineatus feeds on unconsolidated organic flocs freshly decanted from mixed industrial and sewage outfalls. Fish from Buenos Aires had consistently higher standard length ( L S ) and mass ( M T ) slopes ( b = 3·5), condition indexes ( K = 3·01 ± 0·47, mean ± s.d .) and muscle fat content (fat = 23·8 ± 13·8% wet mass, mean ± s.d .) relative to northern fish ( b = 2·7, K = 2·22 ± 0·39, fat = 3·4 ± 3·2% wet mass, respectively), suggesting that sewage‐derived organic matter was an enriched diet, which allowed an enhanced body mass gain and fat accumulation compared to organic‐poor vegetal detritus in the north Paraná area. Buenos Aires fish also showed higher hepato‐somatic indices (mean ± s.d . I H 1·41 ± 0·49 v. 0·70 ± 0·32, respectively), which correlated with their two to three orders of magnitude higher hydrocarbon and polychlorinated biphenyl (PCB) loads, suggesting an enhanced detoxifying metabolism. The northward migration of fatty P. lineatus was evidenced by the presence of clear outliers in the L S and M T relationship, K and fat content along the Paraná River.

Leaf level early assessment of ozone injuries by passive fluorescence and photochemical reflectance index - M. Meroni; V. Picchi; M. Rossini; S. Cogliati; C. Panigada; C. Nali; G. Lorenzini; R. Colombo (International Journal of Remote Sensing, 2008)

Update on the Genus Trichosporon - Thomas C. Chagas-Neto; Guilherme M. Chaves; Arnaldo L. Colombo (Mycopathologia, 2008)

European larch phenology in the Alps: can we grasp the role of ecological factors by combining field observations and inverse modelling? - M. Migliavacca; E. Cremonese; R. Colombo; L. Busetto; M. Galvagno; L. Ganis; M. Meroni; E. Pari; M. Rossini; C. Siniscalco; U. Morra di Cella (International Journal of Biometeorology, 2008)

Genetic diversity and structure of Ethiopian, Yemen and Brazilian Coffea arabica L. accessions using microsatellites markers - Milene Silvestrini; Michele G. Junqueira; Andréa C. Favarin; Oliveiro Guerreiro-Filho; Mirian P. Maluf; Maria B. Silvarolla; Carlos A. Colombo (Genetic Resources and Crop Evolution, 2007)

Cost-effectiveness of pneumococcal vaccination for prevention of invasive pneumococcal disease in the elderly: an update for 10 Western European countries - S. M. A. A. Evers; A. J. H. A. Ament; G. L. Colombo; H. B. Konradsen; R. R. Reinert; D. Sauerland; K. Wittrup-Jensen; C. Loiseau; D. S. Fedson (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Association Between the cfxA Gene and Transposon Tn4555 in Bacteroides distasonis Strains and Other Bacteroides Species - Livia Q. Ferreira; Katia E. S. Avelar; Jessica M. B. D. Vieira; Geraldo R. de Paula; Ana P. V. Colombo; Regina M. C. P. Domingues; Maria C. S. Ferreira (Current Microbiology, 2007)

Systematic GIS-based landslide inventory as the first step for effective landslide-hazard management - A. Colombo; L. Lanteri; M. Ramasco; C. Troisi (Landslides, 2005)

CT—3D rotational angiography automatic registration: A sensitivity analysis - J. Stancanello; C. Cavedon; P. Francescon; P. Cerveri; G. Ferrigno; F. Causin; F. Colombo (Medical & Biological Engineering & Computing, 2005)

First lead isotopic data for cinnabar in the Almadén district (Spain): implications for the genesis of the mercury deposits - Pablo Higueras; José Munhá; Roberto Oyarzun; Colombo C. G. Tassinari; Izabel R. Ruiz (Mineralium Deposita, 2005)

Transcript profiling of transcription factor genes during silique development in Arabidopsis - Stefan de Folter; Jacqueline Busscher; Lucia Colombo; Alessia Losa; Gerco C. Angenent (Plant Molecular Biology, 2004)

Transpositional behaviour of an Ac/Ds system for reverse genetics in rice - R. Greco; P. B. F. Ouwerkerk; R. J. de Kam; C. Sallaud; C. Favalli; L. Colombo; E. Guiderdoni; A. H. Meijer; J. H. C. Hoge†; A. Pereira (Theoretical and Applied Genetics, 2003)

Successful Treatment of an Aspergillus Brain Abscess with Caspofungin: Case Report of a Diabetic Patient Intolerant of Amphotericin B - A. L. Colombo; R. C. Rosas (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Multiple sources for ore-forming fluids in the Neves Corvo VHMS Deposit of the Iberian Pyrite Belt (Portugal): strontium, neodymium and lead isotope evidence - Jorge M. Relvas; Colombo C. Tassinari; José Munhá; Fernando J. Barriga (Mineralium Deposita, 2001)

Genomic changes in transgenic rice (Oryza sativa L.) plants produced by infecting calli with Agrobacterium tumefaciens - M. Labra; C. Savini; M. Bracale; N. Pelucchi; L. Colombo; M. Bardini; F. Sala (Plant Cell Reports, 2001)

Single-strand conformation polymorphism analysis of the glucose transporter gene GLUT1 in maturity-onset diabetes of the young - M. Baroni; F. Sentinelli; O. Massa; S. Romeo; C. Colombo; U. Di Mario; F. Barbetti (Journal of Molecular Medicine, 2001)

Sequence comparison and phylogenetic analysis of fish nodaviruses based on the coat protein gene - L. Dalla Valle; E. Negrisolo; P. Patarnello; L. Zanella; C. Maltese; G. Bovo; L. Colombo (Archives of Virology, 2001)

Early and multiple Ac transpositions in rice suitable for efficient insertional mutagenesis - Raffaella Greco; Pieter B.F. Ouwerkerk; Anke J.C. Taal; Cristina Favalli; Thierry Beguiristain; Pere Puigdomènech; Lucia Colombo; J. Harry C. Hoge; Andy Pereira (Plant Molecular Biology, 2001)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Soil microbial diversity and community structure across a climatic gradient in western Canada - William J. Staddon; Jack T. Trevors; Luc C. Duchesne; Carol a. Colombo (Biodiversity and Conservation, 1998)

Free circulating magnesium and loop diuretics in humans - T. Gozzi; S. Dürler; A. C. Truttman; J. P. Colombo; M. G. Bianchetti (European Journal of Clinical Pharmacology, 1997)

Exopolysaccharide of Nostoc muscorum (Cyanobacteria) in the aggregation of soil particles - G. Zulpa de Caire; M. Storni de Cano; M. C. Zaccaro de Mulé; R. M. Palma; K. Colombo (Journal of Applied Phycology, 1997)